2019
DOI: 10.29271/jcpsp.2019.03.253
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Deficiency is Associated with Poor Glycemic Control

Abstract: The sample size was calculated by using sample size calculating formula available on website 10 by keeping 95% confidence level and 5% margin of error for population of 1,00,000. The minimum sample size was 383 subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Zn is widely distributed in the human body and the most abundant Zn is in muscle (60%), followed by bone (20-30%), skin and hair (8%), and liver (4-6%) [20]. In many patients with LC, diabetes, chronic inflammatory bowel diseases, and chronic kidney diseases, serum Zn levels have been reduced, indicating that they are in a state of Zn deficiency [19,[21][22][23]. Hypozincemia (serum Zn level <55 µg/dL) has been linked to liver carcinogenesis in patients with hepatitis C virus (HCV)-related LC [24].…”
Section: Introductionmentioning
confidence: 99%
“…Zn is widely distributed in the human body and the most abundant Zn is in muscle (60%), followed by bone (20-30%), skin and hair (8%), and liver (4-6%) [20]. In many patients with LC, diabetes, chronic inflammatory bowel diseases, and chronic kidney diseases, serum Zn levels have been reduced, indicating that they are in a state of Zn deficiency [19,[21][22][23]. Hypozincemia (serum Zn level <55 µg/dL) has been linked to liver carcinogenesis in patients with hepatitis C virus (HCV)-related LC [24].…”
Section: Introductionmentioning
confidence: 99%
“…Our patient was also a type 1 diabetic. Low serum zinc levels have been associated with poor glycemic control in both type 1 and 2 diabetics [20,21]. Zinc is a cofactor in the synthesis, storage, and secretion of insulin [20].…”
Section: Discussionmentioning
confidence: 99%
“…Low serum zinc levels have been associated with poor glycemic control in both type 1 and 2 diabetics [20,21]. Zinc is a cofactor in the synthesis, storage, and secretion of insulin [20]. In addition, since zinc is essential in the formation and function of antioxidant enzymes, zinc deficiency may result in an increase in intracellular oxidants and free radicals in diabetics [22].…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic beta-cells, oxidative stress is a central mechanism involved in the alteration of the beta-cell differentiated phenotype under chronic hyperglycemia [3,[54][55][56][57]. Moreover, metal ions play essential physiological roles in beta-cells, and metal dyshomeostasis has been linked with the beta-cell demise in experimental models and was associated with diabetes and its complications in human subjects [58][59][60][61][62][63]. Interestingly, several clinical and epidemiological reports have shown that both type 1 diabetes (T1D) and T2D states are characterized by hypozincemia [64][65][66][67][68][69].…”
Section: Metallothioneins: the Guardians Of Metal And Redox Homeostasismentioning
confidence: 99%